Use of topical insulin to treat refractory neurotrophic corneal ulcers - Suchitra Kumari; Antabha Bandyopadhyay; Taruni Kumari (Journal of Clinical Ophthalmology and Research)
Aim: The aim of the study was to evaluate the efficacy and safety of topical insulin drops in the treatment of refractory neurotrophic keratitis (NK). Materials and Methods: Eight patients with NK refractory to standard medical treatment were selected. Topical insulin drop was prepared by mixing regular insulin in artificial tears with polyethylene glycol and propylene glycol base at a concentration of 1 unit/ml and was prescribed four times daily along with bandage contact lens application. Treatment was continued until persistent epithelial defect (PED) or ulcer resolved and was tapered accordingly. The primary outcome was complete resolution of PED or ulcer. Best corrected visual acuity was assessed and anterior segment photographs were taken. Results: Seven out of 8 eyes showed complete resolution of NK. One of the patient's epithelial defects improved significantly although the wound did not heal completely. No side-effects were reported during the treatment period. Conclusions: Topical insulin may prove to be a simple and effective treatment for refractory NK. This therapy may be extremely useful due to its low cost and high accessibility. Further study is required to determine the clinical efficacy and side effect profile of insulin drops.